RASIONALITAS PENAFSIRAN IBNU âATHIYYAH - Karim, Abdullah (Jurnal Ilmu Ushuluddin, 2013)
Borrowing the definition used by Binyamin Abrahamov for discussion of theology: Rationality is treating any issues by using reason, but whitout giving priority reason. Thus, if it is associated with the interpretation means interpreting the Quran by using reasoning or ijtihad, but without making it as the main point. The use of reason in addition to a history that is valid in the interpretation of the Quran is a necessity. This is caused by the editors who sometimes use the Quran itself ambiguous pronunciation (musytarak / ambiguous) meaning there is even the opposite, or use a word with a specific meaning. However, the interpretation of rationality is limited in scope to understand the meaning or spelling or sentence structure verses (read: the discourse of) the Quran. Not including the use of analogy in legal dig no texts or texts in the Quran.